Pengaruh Implementasi Standar Akuntansi Pemerintahan dan Sistem Informasi Akuntansi Terhadap Kualitas Laporan Keuangan - Rukmi Juwita (Faculty of Economics and Business, University of Pasundan, 2013)
The purpose of this study to determine and analyze (1) influence the implementation of government accounting standards and implementation of accounting information system partially on the quality of financial reporting in areas of the city/county in the province of West Java (2) influence the implementation of government accounting standards and implementation of accounting information systems simultaneously on the quality of financial reporting in the area of the city/county in the province of west Java. The results showed that the Pearson correlation test results to variable implementation of government accounting standards and implementation of accounting information systems have a very strong relationship / linked to the quality of financial statements. Results of regresion testing simultaneously with the partial F test and t-test, showed that the implementation of government accounting standards and implementation of accounting information system significantly affect the quality of financial statements.